2017
DOI: 10.1002/2017jb014525
|View full text |Cite
|
Sign up to set email alerts
|

The 2016 Kumamoto Mw = 7.0 Earthquake: A Significant Event in a Fault–Volcano System

Abstract: The 2016 Kumamoto earthquake sequence occurred on the Futagawa–Hinagu fault zone near the Aso volcano on Kyushu island. The sequence was initiated with two major (Mw ≥ 6.0) foreshocks, and the mainshock (Mw = 7.0) occurred 25 h after the second major foreshock. We combine GPS, strong motion, synthetic aperture radar images, and surface offset data in a joint inversion to resolve the kinematic rupture process of the mainshock and coseismic displacement of the foreshocks. The joint inversion results reveal a uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 74 publications
9
90
0
Order By: Relevance
“…At the northeast end of rupture fault, there is a high productivity asperity where the coseismic rupture terminates and a gap of ∼8 km length, with low productivity values, in between. This gap is consistent with the 10‐km‐long gap of aftershocks reported in Yue et al () who attribute this phenomenon to partial melting in this volcanic region.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…At the northeast end of rupture fault, there is a high productivity asperity where the coseismic rupture terminates and a gap of ∼8 km length, with low productivity values, in between. This gap is consistent with the 10‐km‐long gap of aftershocks reported in Yue et al () who attribute this phenomenon to partial melting in this volcanic region.…”
Section: Resultssupporting
confidence: 92%
“…(b1-c3) Comparison between aftershock productivity distribution and coseismic slip distribution. (b1-b3) Interpolated productivity distributions on the mainshock fault planes from results ofYagi et al (2016),Asano and Iwata (2016), andYue et al (2017). (c1-c3) Slip distributions from the three models.…”
mentioning
confidence: 99%
“…From this sense, the Huya and Minjiang are splay faults associated with the Tazang fault, which is a direct extension of the East Kunlun fault. Similar splay faults were often resolved as hosting the initial rupture of great earthquakes such as the 2001 Kokoxili earthquake (Klinger et al, 2005) or foreshocks such as the 2016 Kumamoto earthquake (Yue et al, 2017). Therefore, the occurrence of the Jiuzhaigou earthquake calls for attention for the future seismic hazard on the Tazang or the East Kunlun fault.…”
Section: Rupture On An Obtuse Branchmentioning
confidence: 99%
“…Many studies have demonstrated that fluids and arc magma exist under the Aso active volcano near the Kumamoto source zone: for example, a high‐temperature (over ~500 °C) anomaly at ~3‐km depth beneath the Aso caldera (Okubo & Shibuya, ), a prominent low‐velocity anomaly indicating a magma chamber (H. Wang et al, ; Xia et al, ; Yu et al, ; Zhao et al, ), a broad low‐viscosity anomaly in the lower crust (Moore et al, ), a large velocity reduction caused by pressurized volcanic fluids (Nimiya et al, ), and volcanic rocks containing components of slab‐derived fluids (Kita et al, ). Coulomb stress changes indicate that the high‐temperature and widespread fluids around the Aso volcano also stopped the rupture of the Kumamoto mainshock (Yue et al, ; Zhang et al, ). It is generally considered that arc magma and fluids can affect the generation of large crustal earthquakes in Japan (e.g., Liu & Zhao, ; Tong et al, ; Zhao, ; Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Geophysical Research: Solid Earth high-temperature and widespread fluids around the Aso volcano also stopped the rupture of the Kumamoto mainshock (Yue et al, 2017;Zhang et al, 2018). It is generally considered that arc magma and fluids can affect the generation of large crustal earthquakes in Japan (e.g., Liu & Zhao, 2015;Tong et al, 2012;Zhao, 2015;Zhao et al, 1996).…”
Section: 1029/2018jb017079mentioning
confidence: 99%